Study on the Influence of Sex Ratio on Ecology Based on Improved Lotka-Volterra Model - Wang, Sihao; Xu, Jiawei; Yang, Haocheng (Transactions on Computer Science and Intelligent Systems Research, 2024)
In a pioneering study of lamprey population dynamics, we employ an enhanced Lotka-Volterra model to illuminate the profound influence of sex ratio shifts on ecosystems. This exploration delves into how such changes affect resource availability, ecosystem equilibrium, and sustainability. We employ dynamic differential equations to simulate population fluctuations among males, females, and predators, incorporating elements like birth rate, mortality rate, competition coefficient, mating success rate, and predation rate. The differential equations are numerically resolved using the Runge-Kutta method, enabling us to analyze population dynamics across various scenarios. Concurrently, we construct Jacobian matrices to appraise ecosystem stability and equilibrium points. The refined Lotka-Volterra model effectively encapsulates the impact of sex ratio variations on reproductive and predation processes, offering profound insights into predator-prey interactions and ecosystem dynamics. Our pivotal discoveries underscore the influence of sex ratio modifications on reproductive capacity, population growth rates, social structure, genetic diversity, and predator-prey relationships. This study emphasizes the criticality of comprehending the repercussions of sex ratio shifts on ecosystems and communities.